1980
DOI: 10.1038/bjc.1980.211
|View full text |Cite
|
Sign up to set email alerts
|

Ortho-toluene sulphonamide and saccharin in the promotion of bladder cancer in the rat

Abstract: Summary.-The importance of the contaminant OTS in the promoting activity of commercial saccharin on rat bladder neoplasia was investigated. OTS, OTS-free and OTS-contaminated saccharin were administered in the drinking water or diet for 2 years to groups of rats pretreated with an intravesical instillation of MNU; OTS alone and OTS-free saccharin were also given to groups of rats not pretreated with MNU.Administration of OTS was not associated with changes in urinary pH, crystalluria or calculus formation, had… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1982
1982
1998
1998

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…After finishing the first batch of MNU (sample A), single doses of 1P5 mg or 2*0 mg of other batches, used both here and in other laboratories, proved to be carcinogenic and produced bladder-cancer incidences of -20% and -400o respectively Mohr et al, 1979;Hicks, 1980;Hooson et al, 1980). This suggested that the MNU sample A may have partially decomposed before we started using it, but its activity had then remained stable.…”
Section: The Intravesicular Instillation Ofmentioning
confidence: 76%
“…After finishing the first batch of MNU (sample A), single doses of 1P5 mg or 2*0 mg of other batches, used both here and in other laboratories, proved to be carcinogenic and produced bladder-cancer incidences of -20% and -400o respectively Mohr et al, 1979;Hicks, 1980;Hooson et al, 1980). This suggested that the MNU sample A may have partially decomposed before we started using it, but its activity had then remained stable.…”
Section: The Intravesicular Instillation Ofmentioning
confidence: 76%
“…It induces hyperplastic lesions and tumors after a single intravesical pulse dose (5mg/kg body weight) or several fractionated lower doses Hicks 1980;Hooson et al 1980;Severs et al 1982;Kunze and Gassner 1986;Kunze et al 1989). It induces hyperplastic lesions and tumors after a single intravesical pulse dose (5mg/kg body weight) or several fractionated lower doses Hicks 1980;Hooson et al 1980;Severs et al 1982;Kunze and Gassner 1986;Kunze et al 1989).…”
Section: N-methyl-n-nitrosoureamentioning
confidence: 99%
“…Focal hyperplasia begins to appear between 2 and 5 weeks (Fukushima and Cohen 1980;Murasaki and Cohen 1983), and by 2 years simple hyperplasia occurs at an incidence of between 23% and 52% (Nakanishi et al 1980a;. Urothelial hyperplasia induced by dietary sodium saccharin is apparently reactive in nature and lacks a preneoplastic potential in adult rats, since most long-term, single-generation studies failed to document tumor development (Schmahl 1973;Nakanishi et al 1980a;Hooson et al 1980;Fig. Sodium saccharin does not provoke urothelial cell necroses, but slightly stimulates urothelial proliferation, leading to a dose-relatedl elevated eH]TdR index of between 0.08% and 0.55% (range of normal values, 0.02%-0.08%; Fukushima and Cohen 1980;Cohen 1981, 1983).…”
Section: Induction Of Regenerative and Reactive Urothelial Hyperplasiamentioning
confidence: 99%
“…Recently, as a component of a larger study, Hooson et al (59) administered o-TS in the drinking water or diet to groups of 63 or 50 female Wistar SPF weanling rats, respectively, at a level equivalent to 70 mg/kg. No evidence of bladder hyperplasia or neoplasia was observed.…”
Section: Toxicology Studiesmentioning
confidence: 99%